2011
DOI: 10.1128/iai.05320-11
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Dimeric GMP Signaling Regulates Intracellular Aggregation, Sessility, and Growth of Ehrlichia chaffeensis

Abstract: Cyclic dimeric GMP (c-di-GMP), a bacterial second messenger, is known to regulate bacterial biofilm and sessility. Replication of an obligatory intracellular pathogen, Ehrlichia chaffeensis, is characterized by formation of bacterial aggregates called morulae inside membrane-bound inclusions. When E. chaffeensis matures into an infectious form, morulae become loose to allow bacteria to exit from host cells to infect adjacent cells. E. chaffeensis expresses a sensor kinase, PleC, and a cognate response regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The role of c‐di‐GMP in controlling extracytoplasmic proteases has been characterized (Kumagai et al ., ; Navarro et al ., ), and membrane and cytoplasmic proteases were associated with aminoglycoside resistance (Hinz et al ., ). Our proteomic analysis revealed that the proteins HslU and ClpA, which are accessories to the proteases HslV and ClpP, are altered when varying the c‐di‐GMP levels.…”
Section: Discussionmentioning
confidence: 98%
“…The role of c‐di‐GMP in controlling extracytoplasmic proteases has been characterized (Kumagai et al ., ; Navarro et al ., ), and membrane and cytoplasmic proteases were associated with aminoglycoside resistance (Hinz et al ., ). Our proteomic analysis revealed that the proteins HslU and ClpA, which are accessories to the proteases HslV and ClpP, are altered when varying the c‐di‐GMP levels.…”
Section: Discussionmentioning
confidence: 98%
“…A direct role for cyclic di‐GMP signalling in enhanced persistence of P. aeruginosa has recently been demonstrated in a chinchilla middle ear infection model (Byrd et al ., 2011). Also bacterial aggregation in host cells, which closely resembles biofilm formation, is mediated by cyclic di‐GMP signalling (Kumagai et al ., 2011). Thus, in bacterial host interactions cyclic di‐GMP signalling seems to regulate the transition between acute and chronic infection, virulence and persistence and maybe even between virulence and commensalism.…”
Section: Virulencementioning
confidence: 99%
“…16,17 Moreover, biofilms represent a big problem when formed on artificial devices used in medicine, such as catheters, stents, orthopedic implants, points of biofilm formation, as the mutant does not display defects in in vitro assays at earlier time points. The role of flagella in biofilm development by motile bacteria varies between species.…”
Section: Introductionmentioning
confidence: 99%